Innovative Biomaterials Based on Collagen-Hydroxyapatite and Doxycycline for Bone Regeneration - Narcisa Mederle; Stefania Marin; Minodora Maria Marin; Elena Danila; Ovidiu Mederle; Madalina Georgiana Albu Kaya; Mihaela Violeta Ghica (Advances in Materials Science and Engineering)
Bone regeneration is a serious challenge in orthopedic applications because of bone infections increase, tumor developing, and bone loss due to trauma. In this context, the aim of our study was to develop innovative biomaterials based on collagen and hydroxyapatite (25, 50, and 75%) which mimic bone composition and prevent or treat infections due to doxycycline content. The biomaterials were obtained by freeze-drying in spongious forms and were characterized by water uptake capacity and microscopy. The in vitro release of doxycycline was also determined and established by non-Fickian drug transport mechanism. Among the studied biomaterials, the most suitable one to easily deliver the drug and mimic bone structure, having compact structure and lower capacity to uptake water, was the one with 75% hydroxyapatite and being cross-linked.